2018
DOI: 10.1002/solr.201800291
|View full text |Cite
|
Sign up to set email alerts
|

A1‐A2 Type Wide Bandgap Polymers for High‐Performance Polymer Solar Cells: Energy Loss and Morphology

Abstract: Introducing electron‐withdrawing groups onto donor‐acceptor (D‐A) type conjugated materials is a commonly used method for lowering their highest occupied molecular orbital (HOMO) energy level to achieve higher open circuit voltage (Voc) in polymer solar cells (PSCs). However, this method is rather costly due to the tedious synthesis and low yield involved in preparing the target monomers. Here, a novel design concept of using two different acceptor units to construct acceptor1‐acceptor2 (A1‐A2) type polymers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…However, for both the PBDB‐T:SM‐X and PBDB‐T:SM‐XY blends, the emission peak of PBDB‐T still exists to some extent and is even stronger than that of the neat PBDB‐T film excited at 460 nm (Figure S14a, Supporting Information). These results suggest that proficient energy transfer occurs in PBDB‐T:SM‐X and PBDB‐T:SM‐XY blends, but that charge (electron/hole) transfer is involved in the PBDB‐T:SM‐Y blend 6c,e,21. Note that the ITIC:SM‐axis binary blends excited at 460 nm also showed that similar emission trends depend on the type of SM‐axis molecules present, i.e., the energy transfer from SM‐X or SM‐XY to ITIC and charge transfer between ITIC and SM‐Y (Figure b and Figure S14b, Supporting Information).…”
Section: Resultsmentioning
confidence: 90%
“…However, for both the PBDB‐T:SM‐X and PBDB‐T:SM‐XY blends, the emission peak of PBDB‐T still exists to some extent and is even stronger than that of the neat PBDB‐T film excited at 460 nm (Figure S14a, Supporting Information). These results suggest that proficient energy transfer occurs in PBDB‐T:SM‐X and PBDB‐T:SM‐XY blends, but that charge (electron/hole) transfer is involved in the PBDB‐T:SM‐Y blend 6c,e,21. Note that the ITIC:SM‐axis binary blends excited at 460 nm also showed that similar emission trends depend on the type of SM‐axis molecules present, i.e., the energy transfer from SM‐X or SM‐XY to ITIC and charge transfer between ITIC and SM‐Y (Figure b and Figure S14b, Supporting Information).…”
Section: Resultsmentioning
confidence: 90%
“…By calculating the dihedral angle, dipole moment, and surface electrostatic potential of isomers, the differences in molecular conformation and electronic properties can be deeply analyzed and thus guide more efficient molecular design. [ 37,38 ]…”
Section: Methodsmentioning
confidence: 99%
“…moment, and surface electrostatic potential of isomers, the differences in molecular conformation and electronic properties can be deeply analyzed and thus guide more efficient molecular design. [37,38] In this work, fluorinated benzotriazole (ffBTz) and carboxylate-substituted thiophene were used to construct two polymer donors, PBTz4T2C-a and PBTz4T2C-b. The difference between PBTz4T2C-a and PBTz4T2C-b was the substitution position of the carboxylate groups on 4T2C unit.…”
mentioning
confidence: 99%
“…E loss = E opt -eV OC (where E opt is the optical gap of the absorber, e is the elementary charge) [14][15][16][17][18] . Shockley-Queisser (SQ) theory [19] predicts the theoretical value of 0.25-0.30 eV in the solar cells. However, most of highly efficient OSCs suffer from high E loss in the range of 0.6-1.1 eV, leading to the much lower V OC than inorganic and perovskite solar cells (>1.0 V).…”
Section: Introductionmentioning
confidence: 99%